Blackout analysis of Mars entry missions. (10th December 2020) - Ramjatan, Sahadeo; Lani, A.; Boccelli, S.; Van Hove, B.; Karatekin, Ö.; Magin, T.; Thoemel, J.
Abstract: Abstract : A new methodology to accurately and efficiently examine the radio frequency blackout phenomenon during the hypersonic reentry process is introduced and validated. The current state-of-the-art thermochemical modelling of CO_2 flows is reviewed and one-dimensional stagnation line studies are performed in order to determine a suitable chemical mechanism for the electron density modelling. Hypersonic computational fluid dynamics (CFD) simulations are performed with a simplified chemical model including only neutral species, in order to calculate the flow field surrounding the ExoMars Schiapparelli module in flight conditions. A novel decoupled CFD approach is then applied where the calculation of the electron density is performed separately using a computationally inexpensive Lagrangian approach. Subsequently, a ray tracing algorithm is applied in order to model the propagation of electromagnetic waves in the wake flow past the ExoMars vehicle accounting for collisions between electrons and gas particles. The numerical results of the proposed novel approach for blackout analysis consisting of CFD, Lagrangian and ray tracing algorithms are in good agreement with the flight data.